2014
DOI: 10.4028/www.scientific.net/amr.889-890.303
|View full text |Cite
|
Sign up to set email alerts
|

Design of Automatic Buckle Machine for Double Bag Packaging Line

Abstract: Double bag packaging line which is widely used in packing line is a packing type. There are traditional double bag packaging line and automatic packaging line. Among them, the automated packaging line processes include: On the bag, filling, bayonet, seaming, transporting, stacking and other processes. However, bayonet is an essential process in packaging line. The design of automatic buckle machine plays a key role in reducing labor intensity, improving production efficiency of filling line and ensuring produc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Feasible application-specific methods for signal measurement to master future systems are thus indispensable [1][2][3][4][5][6]. Unfortunately, the wire threading through the die mold for theelongation process has not been automatizeduntil now [7][8][9][10]. For advanced automation study related to this issue, many papers can be found in the literature [11][12][13][14][15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…Feasible application-specific methods for signal measurement to master future systems are thus indispensable [1][2][3][4][5][6]. Unfortunately, the wire threading through the die mold for theelongation process has not been automatizeduntil now [7][8][9][10]. For advanced automation study related to this issue, many papers can be found in the literature [11][12][13][14][15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…Currently, various functionalities required in industry have made the automation system extremely varied. For this reason, the modern automation systems are moving toward very high complexity, depending on the system structure [1][2][3][4][5][6]. Unfortunately, it is found that the copper wire elongation system for threading through the die mold is not completely automated so far in industry.…”
Section: Introductionmentioning
confidence: 99%